2022
DOI: 10.3390/pr10020353
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nitrogen Conservation Measures on the Nitrogen Uptake by Cotton Plants and Nitrogen Residual in Soil Profile in Extremely Arid Areas of Xinjiang, China

Abstract: This study researched the effects of using various nitrogen (N) conservation measures on the residual characteristics of nitrate and ammonium N in soil and the associated N uptake by cotton plants. A field experiment with six treatments was conducted, as follows, no N application (DT1), conventional N application (DT2), 60% conventional N application combined with DCD (DT3), 60% conventional N application combined with NBPT (DT4), 60% conventional N application combined with cotton straw returning (DT5), and 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…Heavier bolls in wider spacing may be because of less competition amongst crop plants, resulting in efficient consumption of all resources ( Table 3 ). These findings are found to be similar to Alfaqeih et al (2002) , Ali et al (2007) , Rafi et al (2015) , Alsalem et al (2022) , and Zhi et al (2022) . They reported that wider space increased the number of branches per plant and boll weight which was due to less competition between plants.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Heavier bolls in wider spacing may be because of less competition amongst crop plants, resulting in efficient consumption of all resources ( Table 3 ). These findings are found to be similar to Alfaqeih et al (2002) , Ali et al (2007) , Rafi et al (2015) , Alsalem et al (2022) , and Zhi et al (2022) . They reported that wider space increased the number of branches per plant and boll weight which was due to less competition between plants.…”
Section: Discussionsupporting
confidence: 88%
“…Several investigations have been performed to investigate the impacts of plant spaces ( Bednarz et al, 2007 ; Hafeez et al, 2018 ; Fahad et al, 2021b ) and N fertilization rate ( Boquet and Breitenbeck, 2000 ; Bondada and Oosterhuis, 2001 ) in terms of cotton yield and its yield components. Others have observed interactions between plant space and N fertilization ( Ali et al, 2007 ; Zaman et al, 2021 ; Van Der Sluijs, 2022 ; Zhi et al, 2022 ). The impacts of plant space and N rates were explored in the current study, with an emphasis on their interaction.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The model of high yield under high fertilizer application will result in a low fertilizer-utilization rate, and to some extent, it will bring about farmland pollution [38]. Therefore, with the premise of maintaining cotton yield, reducing nitrogen application and adopting protective measures can improve cotton NUE and reduce the risk of nitrogen point source pollution [42,43].…”
Section: Discussionmentioning
confidence: 99%